THE CONCEPT OF FUNCTION IN BASIC EDUCAATION TROUGH SEMIOTIC REPRESENTATION REGISTERS - Paulo César Oliveira; Rogério Fernando Pires (Reflexão & Ação, 2012)
The present study aimed to investigate which categories of written records are mobilized by students in the 9th grade in elementary school involved in mathematical activities related to functional thinking, the main theoretical ideas of the theory of records Semiotic Representation of Raymond Duval. The study consisted of the application and analysis of the activities that comprised a didactic sequence was performed with a group consisting of 38 students in 9th grade of basic education of a public school, located in the city of Pilar do Sul in São Paulo. The results found after analyzing the data show that the records were the most used multifunctional discursive representation and records monofunctional discursive representation and, although the relationship between congruence and no congruence of representations of a mathematical object, delimit the understanding of same.